Poster 102: Assessment of Safety and Efficacy of Intravenous and Intraarticular Administration of Tranexamic Acid in Arthroscopic Surgery: A Systematic Review of Randomized Controlled Trials. Issue 7 (30th July 2022) - Johnson, Emma; Kemler, Bryson; Walley, Kempland; Ciccotti, Michael; Hammoud, Sommer; Johns, William
Objectives: Tranexamic acid (TXA) is widely used in arthroplasty procedures and has recently gained popularity as an adjunct for improving perioperative outcomes after arthroscopic procedures. However, the safety, side-effect profile, and efficacy of various routes of administration (intravenous and intraarticular) of tranexamic acid in arthroscopic surgery have not been clearly delineated. The objectives of this study are to analyze the available literature on overall safety, efficacy, and complications such as deep vein thrombosis, pulmonary embolus, and infection following administration of intravenous (IV) or intraarticular (IA) tranexamic acid in arthroscopic procedures. Methods: A literature search in agreement with the Preferred Reporting Items from Systematic Reviews and Meta-Analyses (PRISMA) protocol was performed to retrieve randomized controlled trials examining the use of tranexamic acid at the time of arthroscopic procedures. Inclusion criteria included randomized controlled trials (RCT), published at any time, which report adverse clinical outcomes, including deep vein thrombosis, pulmonary embolus, and adverse reactions following arthroscopic procedures, in which patients were randomized into an experimental group who received TXA (either intravenously or via intra-articular injection) preoperatively and a control group who did not receive TXA. The exclusion criteria were those studies that were non-RCT and did not assess outcomes following arthroscopic procedures. The studied outcomes included: thromboembolic events, adverse drug reactions, postoperative drain output, VAS pain scores, and joint aspiration requirements. Results: Thirteen prospective randomized controlled trials met inclusion criteria for analysis and were included in this review. These studies examined a total of 1, 159 arthroscopic procedures, comprised of 174 hip arthroscopy procedures, 810 knee arthroscopy procedures for ACL reconstruction, 103 knee arthroscopy procedures for meniscectomy or repair, and 72 shoulder arthroscopy procedures for rotator cuff repair. Tranexamic acid use in arthroscopic procedures resulted in no increase in thromboembolic events or adverse drug reactions, with no thromboembolic events or adverse drug reactions reported across the 1, 159 procedures. Tranexamic acid in IV and IA forms used in ACL reconstruction reduced 24-hour postoperative drain output (-48.47cc; P=0.001 in IV TXA and -39.11cc, P=0.004 in IA TXA group when compared to control) and improved VAS pain scores in the early postoperative period at 1 week (-1.4, P<0.00001 in IV TXA and -1.68, P<0.00001 in IA TXA when compared to control) as demonstrated in Figure 1a and 1b. Further, IV TXA resulted in a significant reduction in postoperative aspiration requirement compared to control (Odds Ratio 0.37, P=0.02) following ACL reconstruction as demonstrated in Figure 2. Conclusions: The use of IV or IA TXA in arthroscopic surgery including rotator cuff repair, meniscus, femoroacetabular impingement surgery, and ACL reconstruction is safe and confers no increased risk of thromboembolic events. IV and IA TXA have proven to be effective in reducing postoperative drain output and even reducing pain in the early postoperative period following ACL reconstruction. Finally, IV TXA has been shown to reduce the need for postoperative aspiration following ACL reconstruction.